산양삼 자조금 도입을 위한 산양삼 생산자의 인식 연구 - 김태희; Taehui Kim; 손미정; Mijeong Son; 김주미; Jumi Kim (한국산림과학회지, 2025)
산양삼은 특별관리임산물로 유일하게 지정되어 품질관리 체계에 따라 관리되고 있는 고부가가치 약용식물이다. 그러나 과장 광고 및 원산지 둔갑 등으로 소비자 신뢰가 저하되고 있어 지속가능한 발전을 위한 새로운 접근이 필요하다. 이에 본 연구는 산양삼 자조금 제도의 도입 가능성을 검토하고, 이를 위한 생산자의 인식을 분석하였다. 2024년 10월 설문조사를 실시하여 총 93부의 응답을 분석에 활용하였으며, 심층 인터뷰는 생산자단체의 주요 관계자를 대상으로 진행하였다. 연구결과, 전체 응답자의 66.7%가 자조금 도입을 지지하였으며, 재배면적(m²)을 기준으로 한 거출방식을 가장 선호하였다. 자조금에 대한 인지정도와 선호정도, 재배경력, 연간 판매액은 도입 필요성 인식에 유의한 영향을 미친 반면, 생산량, 재배면적, 주소득 여부는 유의하지 않았다. 산양삼 산업의 지속가능한 발전을 위해 생산자 주도의 자조금 체계 구축이 필요하며, 이를 위해 생산자 교육 및 투명한 유통구조 확립 등의 기반이 요구된다. 본 연구는 산양삼의 특성을 고려한 자조금 제도 설계와 실행을 위한 방향성을 제시하였으며, 향후 후속 연구와 정책 수립 등에 기초자료로 활용될 수 있을 것으로 사료된다. Wild-simulated ginseng is a high-value medicinal plant and the only plant designated as a Specially Managed Forest Product in Korea's quality management system. However, consumer trust has been diminished as a result of exaggerated advertisements and falsifications of the product’s origins, highlighting the need for a new approach to the sustainable development of the ginseng industry. This study investigated producers’ perceptions, aiming to examine the feasibility of introducing a check-off program for wild-simulated ginseng. Ninety-three responses were collected from surveys conducted in person and online in October 2024. In-depth interviews were conducted with representatives from producer organizations. Producers’ perceptions were examined through frequency and cross-tabulation analyses using SPSS 26. A total of 66.7% of the respondents supported the introduction of the check-off program. Cultivation area (m²) was the most-preferred (65.6%) standard for contributing to the check-off program. Establishing a producer-led check-off program is essential for sustainably developing the wild-simulated ginseng industry. This requires improving producer education and establishing a transparent distribution structure. This study’s findings can serve as a reference for related future research and policy discussions.